Unicorns and germs - Citro, Asia (Citro, Asia. Zoey and Sassafras, 2018)
An earthquake shakes Zoey's house. Or maybe it's a unicorn-quake? An enormous new friend arrives in a lot of pain, and it's getting worse every day. Zoey must work with her mom and Sassafras to find a cure--and quickly!--